Unique Biradical Intermediate in the Mechanism of the Heme Enzyme Chlorite Dismutase - Püschmann, Julia (2022)
Funding Information: This research was supported by the grant NWO–CW 711.014.006 from the Council for Chemical Sciences of The Netherlands Organization for Scientific Research. S.T. acknowledges the support from the Project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular) funded by FEDER funds through COMPETE 2020─Programa Operacional Competitividade e Internacionalização (POCI) and by national funds through FCT─Fundação para a Ciência e a Tecnologia and from the European Union’s Horizon 2020 Research and Innovation Program through TIMB3 (grant agreements no 810856). This work is dedicated to the late Prof. Simon de Vries, who pioneered the development of the rapid kinetic techniques that have been seminal in this study. Publisher Copyright: © 2021 The Authors. Published by American Chemical Society.